Artificial periodic irregularities in the high‐latitude ionosphere excited by the HAARP facility. Issue 7 (15th July 2016) - Bakhmetieva, N. V.; Grach, S. M.; Sergeev, E. N.; Shindin, A. V.; Milikh, G. M.; Siefring, C. L.; Bernhardt, P. A.; McCarrick, M.
Abstract: We present results of the new observations of artificial periodic irregularities (APIs) in the ionosphere using the High Frequency Active Auroral Research Program (HAARP) heating facility carried out in late May and early June 2014.The objective of this work is to detect API using high‐latitude facility and analyze possible differences of the temporal and spatial variations of the API echoes in the high (HAARP) and middle (Sura) latitudes. Irregularities were created by the powerful wave of X mode and were sounded using the short probing pulses signals of X mode. API echoes were observed in the D, E, and F regions of the ionosphere. Amplitudes and characteristic times of the API echoes were measured. The API growth and decay times at HAARP (high latitudes) observed were similar to those at the Sura heating facility (midlatitudes). Key Points: API experiments were carried out at the HAARP facility, while the Bragg backscattering was observed Characteristics of the signals scattered by API in the D and E regions were measured The ionospheric parameters could be restored from the API measurements